Clinical and molecular features of rapidly progressive chronic hypersensitivity pneumonitis - Horimasu, Yasushi; Ishikawa, Nobuhisa; Iwamoto, Hiroshi; Ohshimo, Shinichiro; Hamada, Hironobu; Hattori, Noboru; Okada, Morihito; Arihiro, Koji; Ohtsuki, Yuji; Kohno, Nobuoki (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Background: Chronic hypersensitivity pneumonitis (CHP) is characterized by varying degrees of inflammation and fibrosis of the lungs caused by a variety of inhaled antigens. Despite extensive efforts to minimize exposure to the antigens, patients with CHP sometimes experience rapid deterioration of their pulmonary functions, resulting in death within a few years. Objectives: This study aimed to define clearly the clinical and molecular features of patients with rapidly progressive CHP. Methods: Annual decline in pulmonary functions and its association with clinical variables was evaluated in 43 patients with CHP. The RNA from frozen lung specimens of nine patients with rapidly progressive CHP and normal control subjects was profiled using Illumina HumanWG-6 v3 Expression BeadChips, and an Ingenuity Pathway Analysis was performed to identify the altered functional and canonical signaling pathways. Results: Patients with more than 10% annual decline in forced vital capacity and those with more than 15% annual decline in diffusion capacity for carbon monoxide showed significantly poor overall survival rates (p=0.002 and p=0.001, respectively). According to the gene expression analysis, 160 genes, including cystatin SN (CST1), ephrin-A2 (EFNA2), and wingless-type MMTV integration site family, member 7B (WNT7B) were upregulated, and pathways related to inflammatory responses and autoimmune diseases were differentially expressed. Conclusion: Greater annual decline in pulmonary function can predict poorer prognosis of patients with CHP. Genes and pathways related to inflammatory responses and autoimmune diseases have potential roles in the pathogenesis of rapidly progressive CHP, suggesting their potential as diagnostic biomarkers and/or therapeutic targets.